Semiotik dan dinamika sosial budaya Ferdinand de Saussure, Roland Barthes, Julia Kristeva, Jacques Derrida, Charles Sanders Peirce, Marcel Danesi & Paul Perron, dll. - Hoed, Benny H. (Komunitas Bambu, 2011)
Study on socioculture from semiotics perspective in Indonesia.